1988
DOI: 10.1111/j.1751-1097.1988.tb02769.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Phthalocyanines‐x. Syntheses and Analyses of Sulfonated Phthalocyanines

Abstract: Abstract-Synthetic methods to obtain selectively sulfonated metallo phthalocyanines are compared. Both condensation and direct sulfonation procedures lead to mixtures of mono-to tetrasulfonated products which are resolved by reverse phase liquid chromatography in buffered aqueous-methanol. The proportion of sulfonated derivatives is examined as a function of the starting reagents in the case of the condensation method. and as a function of the temperature and reaction time in the case of the direct sulfonation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
95
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(98 citation statements)
references
References 13 publications
3
95
0
Order By: Relevance
“…The main characteristic absorption peaks of Fe(III)PcTs were shown in figure 1.Infrared spectrum of Fe (III)PcTs mainly included: (1) The absorption peak at 3441cm -1 is hydroxyl stretching vibration peak, indicated that metal phthalocyanine contains crystal water; (2) Absorption peak at 1725cm -1 showed frame vibration octave band of benzene ring; the absorption peak at 1639cm -1 appear absorption peak indicated phthalocyanine ring of C=C stretching vibration, absorption peak at 1417cm -1 , indicated that phthalocyanine ring C=N stretching vibration, hence explained the existence of phthalocyanine ring; 1116cm is multiple vibration absorption peak sulfonic group, indicating sulfonic group substituent.These vibrations are consistent with the literature [10], which proved that the preparation of samples has the structure of Fe (III) PcTs. [11].In Fe (III) PcTs molecule, center metal ion atom and the N atom have different strength and bond length, make some changes have taken place in the lattice constant of crystal, which result in some changes of the the diffraction peaks and relative position in the XRD spectra of Fe(III)PcTs compared with Fe (II) the Pc, and its main crystal phase is phthalocyanine crystal structure.…”
Section: Ft -Ir Spectrum Of Iron(iii) Tetrasulfophthalocyaninesupporting
confidence: 92%
“…The main characteristic absorption peaks of Fe(III)PcTs were shown in figure 1.Infrared spectrum of Fe (III)PcTs mainly included: (1) The absorption peak at 3441cm -1 is hydroxyl stretching vibration peak, indicated that metal phthalocyanine contains crystal water; (2) Absorption peak at 1725cm -1 showed frame vibration octave band of benzene ring; the absorption peak at 1639cm -1 appear absorption peak indicated phthalocyanine ring of C=C stretching vibration, absorption peak at 1417cm -1 , indicated that phthalocyanine ring C=N stretching vibration, hence explained the existence of phthalocyanine ring; 1116cm is multiple vibration absorption peak sulfonic group, indicating sulfonic group substituent.These vibrations are consistent with the literature [10], which proved that the preparation of samples has the structure of Fe (III) PcTs. [11].In Fe (III) PcTs molecule, center metal ion atom and the N atom have different strength and bond length, make some changes have taken place in the lattice constant of crystal, which result in some changes of the the diffraction peaks and relative position in the XRD spectra of Fe(III)PcTs compared with Fe (II) the Pc, and its main crystal phase is phthalocyanine crystal structure.…”
Section: Ft -Ir Spectrum Of Iron(iii) Tetrasulfophthalocyaninesupporting
confidence: 92%
“…Therefore, many substituted Pcs have been synthesized. [16][17][18][19] We have synthesized a novel AlPc, 12 and the PDT e±cacy of AlPc against the human umbilical cord blood endothelial cell (HUVEC) has been assessed in order to study its potential application in treatment of choroidal neovascularization (CNV). 20 In this study, the interaction between AlPc and BSA/HSA by°uorescence and UVvisible spectroscopic method were further assessed in aim to explore the potential application of AlPc in PDT.…”
Section: Introductionmentioning
confidence: 99%
“…Solov'eva et al (25) (8) with base in CHCI3 likewise gave l-(3,4-dibromophenylsulfonyl)imidazole (13) and I -(3,4-dibromophenylsulfonyl)indole (14) in 34 and 50% yields, respectively (Scheme l). The low yield of 11 As expected Pc 19 proved to be resistant to solvolysis, but Pc sulfonamides 20 and 21 were readily converted to phthalocyanine-2,9,1 6,23tetrasulfonic acid (24) 3,4-Dibromobenzenesulfonyl chloride (2) To a flask containing l,2-dibromobenzene (1) (20 …”
Section: Resultsmentioning
confidence: 99%
“…2). Although phthalocyanine -2,9,1 6,23 -tetr asulfonic acid is commercially available as a mixtufe of isomers, it has been shown that phthalocyanine-2-sulfonic acid ard plrthalocyanine-2,9-disulfonic acid are more effective for direct cell kill (3)(4)(5)(6)(7)(8)(9) …”
mentioning
confidence: 99%